2020
DOI: 10.1111/bph.15139
|View full text |Cite
|
Sign up to set email alerts
|

Exploring microRNAs in diabetic chronic cutaneous ulcers: Regulatory mechanisms and therapeutic potential

Abstract: Diabetic chronic cutaneous ulcers (DCU) are one of the serious complications of diabetes mellitus, occurring mainly in diabetic patients with peripheral neuropathy. Recent studies have indicated that microRNAs (miRNAs/miRs) and their target genes are essential regulators of cell physiology and pathology including biological processes that are involved in the regulation of diabetes and diabetes-related microvascular complications. in vivo and in vitro models have revealed that the expression of some miRNAs can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 153 publications
(198 reference statements)
0
11
0
Order By: Relevance
“…The chronic wound formation process is also regulated epigenetically by miRNAs controlling inflammatory responses via the modulation of signaling pathways. Wnt/β-catenin, NF-κB, PI3K/Akt/mTOR, TGF-β/Smad and VEGF pathways are regulated by miRNAs during chronic wound healing [104]. Immune system in chronic wound healing.…”
Section: Chronic Wound Healingmentioning
confidence: 99%
“…The chronic wound formation process is also regulated epigenetically by miRNAs controlling inflammatory responses via the modulation of signaling pathways. Wnt/β-catenin, NF-κB, PI3K/Akt/mTOR, TGF-β/Smad and VEGF pathways are regulated by miRNAs during chronic wound healing [104]. Immune system in chronic wound healing.…”
Section: Chronic Wound Healingmentioning
confidence: 99%
“…Previous studies have confirmed that ncRNAs are differentially expressed in patients with diabetes and are closely related to the occurrence and development of the disease. 113,115,116 Lin et al 88 showed that the serum levels of miR-217 in DFU patients was significantly upregulated compared with those of healthy individuals. Moreover, as the Wagner grade increases, the serum miR-217 level gradually increases.…”
Section: The Application Prospects Of Ncrna In Diagnosis and Treatmentmentioning
confidence: 99%
“…Apoptotic cells release chemotactic signaling molecules such as lysophosphatidylcholine (LPC) to attract macrophages to the site of injury; however, when not adequately cleared, these immune cells produce chronic inflammation [49,50]. Chronic wounds, such as diabetic wounds, have decreased PI3K/AKT activity with excessive endothelial and keratinocyte apoptosis while also displaying impaired clearance of apoptotic debris due to immune system dysregulation [51][52][53][54]. Pressure ulcers show a similar downregulation in PI3K/AKT [28].…”
Section: Cellular Deformation and Apoptosismentioning
confidence: 99%